Research of methods for improving energy efficiency and emissions reduction in distribution station of natural gas transmission network - Rapolas Tučkus; Artur Rogoža (Mokslas: Lietuvos Ateitis, 2023)
The global energy crisis, rising energy demand and climate warming make it imperative to find ways to recover energy that is not being put to beneficial use, to reduce primary and final energy consumption, and to reduce emissions. An important part of Lithuania’s energy sector is the natural gas sector and its transmission network, including the gas distribution stations (GDS). It is the GDS that has an unexploited potential for energy recovery, as the gas pressure is reduced through the use of gas pressure regulators, where the potential energy in the highpressure gas is not utilized in a useful way, and the necessary heating of natural gas is carried out through the use of natural gas boilers, with additional environmental pollution. The aim of the study is to analyse the gas distribution station, to find the areas of the station where potential energy is not being used and the environment is being polluted, and to propose reasonable solutions. Following a literature review, alternative technical solutions are selected: turbine-expander, conversion of the gas preheating system from gas boilers to a geothermal heat pump, use of solar collectors, photovoltaic solar cells. In order to assess the potential of technological solutions to improve the efficiency of the DSS and reduce emissions, a multi-criteria analysis of the proposed solutions is carried out, where the measures under evaluation are analysed in energy, economic and environmental terms. The energy assessment analyses the energy consumption, the economic assessment calculates the net present value (NPV) of the investment for each solution and the environmental assessment examines the environmental impact of the proposed measures over their life cycle. Based on the results of the multicriteria analysis, the systems best suited to the object of study (GDS) are recommended.